2021
DOI: 10.1002/nano.202100188
|View full text |Cite
|
Sign up to set email alerts
|

Controlling hydrocarbon transport and electron beam induced deposition on single layer graphene: Toward atomic scale synthesis in the scanning transmission electron microscope

Abstract: Focused electron beam induced deposition (FEBID) is a direct write technique for depositing materials on a support substrate akin to 3D printing with an electron beam (e-beam). Opportunities exist for merging this existing technique with aberration-corrected scanning transmission electron microscopy to achieve molecular-or atomic-level spatial precision. Several demonstrations have been performed using graphene as the support substrate. A common challenge that arises during this process is e-beam-induced hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Raising the sample temperature has several consequences. First, it evaporates unwanted hydrocarbon contamination from the graphene surface, [20,[39][40][41] which is a critical concern for fabrication at this scale. Second, it promotes the spontaneous diffusion of adatoms from the parent nanoparticles that can then migrate across the surface and bond with the undercoordinated carbon atoms generated by e-beam ejection.…”
Section: Effects Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Raising the sample temperature has several consequences. First, it evaporates unwanted hydrocarbon contamination from the graphene surface, [20,[39][40][41] which is a critical concern for fabrication at this scale. Second, it promotes the spontaneous diffusion of adatoms from the parent nanoparticles that can then migrate across the surface and bond with the undercoordinated carbon atoms generated by e-beam ejection.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…[15][16][17][18][19] This technique appears generalizable in that many different source elements could be inserted into the graphene; however, the distance from the source material was limited to a few nanometers. In a previous publication, [20] we also broached the topic of contamination and sample cleanliness from the perspective of STEM EBID and suggested a method for preventing the ingress of unwanted hydrocarbon contaminants from elsewhere on the sample. Notably, the contaminants were found to migrate along the graphene surfaces and not through the vacuum, which enabled e-beam-deposited barriers to be sufficient to prevent further contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The initial heating has been shown to remove surface hydrocarbon contamination [65][66][67] and the sustained elevated temperature is conjectured to combat further hydrocarbon deposition that has been observed on what appears to be clean graphene. [68] The state of the sample after this procedure is shown in Figure 4a where we observe a majority of bilayer graphene suspended over an aperture in the e-chip with a number of wrinkles.…”
Section: Growth Of 2d Nanoplateletsmentioning
confidence: 99%
“…Previous work in this context highlights the role of mobile carbon adatoms that spontaneously heal vacancies and larger structural defects. , At the same time, rapidly diffusing vacancies can markedly change the behavior of graphene at high temperatures . The e-beam patterning of corrals can influence the influx of hydrocarbon contamination or provide a trap for long-range vacancy diffusion. The dynamics of these factors are clearly dependent on the sample temperature, and here, we have demonstrated that temperature can also be used to influence the supply of source atoms.…”
mentioning
confidence: 99%
“…To simplify matters further, here we work with 2D materials where, instead of looking at projected columns of atoms (as in a 3D crystal), each atom can be uniquely identified in the image. The most robust and well-studied 2D material is graphene, and many studies have been carried out to find ways to clean and image contamination-free graphene. With these advancements, which act to mitigate major alterations to the specimen, minor alterations at the atomic scale can be observed and studied. Some examples of these atomic scale dynamics are shown in Figure a–d: the spinning of a Si molecular rotor, the dynamic rearrangement of a Si 6 cluster embedded in a graphene nanopore, the movement of a 3-fold coordinated Si dopant in graphene, and vacancy diffusion in graphene .…”
mentioning
confidence: 99%